Four new species of Nemobiinae from China (Orthoptera, Gryllidae, Nemobiinae) - Li, Kai; He, Zhuqing; Liu, Xianwei (Zootaxa, 2010)
Four new species of the cricket subfamily Nemobiinae from China are described. They are Homonemobius nigrus sp. nov., Speonemobius sinensis sp. nov., Polionemobius annulicornis sp. nov. and Pteronemobius yunnanicus sp. nov. All type specimens are deposited in East China Normal University, Biology of History Museum (HSNU); Shanghai Entomological Museum (IEAS) and Shanghai Normal University (SHNUC).